RESILIENSI AKADEMIK SISWA/SISWI KELAS VII DAN VIII SEKOLAH MENENGAH PERTAMA SANTO ANDREAS TAHUN AJARAN 2020/2021 - Dwi Murtiningrum; Yoseph Pedhu (Universitas Katolik Indonesia Atma Jaya, 2021)
Academic resilience is the ability of students to adapt to academic stress which includes components of emotion regulation, impulse control, optimism, empathy, problem-causing analysis, self-efficacy and reaching out. The purpose of this study was to describe the academic resilience of students in grades VII and VIII of Saint Andreas Junior High School for the academic year 2020/2021. The results showed that the academic resilience of students for the academic year 2020/2021 during distance learning was in the high category with a percentage of 64%. Component analysis shows that the highest component is the empathy component with a total score of 1,885 and the lowest component is the problem-causing analysis component with a total score of 1,670.